The Association of Countermovement Jump, Isometric Mid-Thigh Pull, and On-Ice Sprint Performance in University Level Female and Male Ice Hockey Athletes - Stephen Cornish; Matthew Asmundson; Joanne Parsons; Trisha Scribbans (International Universities Strength and Conditioning Association, 2024)
On-ice skating sprint performance is a significant predictor and requirement for playing at the highest levels of hockey. The purpose of this study was to determine the relationship between maximum and dynamic strength measures and on-ice sprint performance in university level ice hockey athletes. Both male (n=18) and female (n=13) hockey players participated in this study. The off-ice measures included two assessment procedures utilizing a force plate; an isometric mid-thigh pull (IMTP) to assess maximum strength and a countermovement jump (CMJ) to assess dynamic strength. Both off-ice measures were analyzed from both a relative (CMJr and IMTPr) and absolute (CMJa and IMTPa) perspective. The on-ice measures were 7.71m and 15.42m sprint times. Pearson product moment correlations were used to quantify the relationships between variables. CMJa (r = -0.56 to -0.61), IMTPa (r = -0.65 to -0.67) and IMTPr (r = -0.55) were significantly correlated (p < 0.05) with on-ice sprint performance. When analyzed by sex, no significant relationships (p > 0.05) were observed between CMJ measures and on-ice sprint times. No significant relationships (p > 0.05) were observed between IMTP measures and on-ice sprint times when individually analyzing male participants, while significant relationships (p < 0.05) were observed in females between IMTPa (r = -0.70 to -0.71) and IMTPr (r = -0.68 to -0.71) and on-ice sprint times. It is concluded that both maximum and dynamic strength are important factors in on-ice sprint performance in hockey players. Furthermore, maximum strength seems to be an important characteristic in on-ice sprint ability in females.